Increase in proapoptotic activity of inhibitory PAS domain protein via phosphorylation by MK2. (13th November 2017) - Kasai, Shuya; Richardson, Mary J. E.; Torii, Satoru; Yasumoto, Ken‐ichi; Shima, Hiroki; Igarashi, Kazuhiko; Itoh, Ken; Sogawa, Kazuhiro; Murayama, Kazutaka
Abstract : Inhibitory PAS domain protein (IPAS) is a bifunctional protein that downregulates hypoxic gene expression and exerts proapoptotic activity by preventing prosurvival activity of Bcl‐xL and its related factors. Proapoptotic activity of IPAS is attenuated by the activation of the PINK1‐Parkin pathway, and involved in neuronal degeneration in an experimental mouse model of Parkinson's disease. The current study shows that phosphorylation of IPAS at Ser184 by MAPK‐activated protein kinase 2 (MK2 or MAPKAPK2) enhances the proapoptotic function of IPAS. Perinuclear clustering of mitochondria and activation of caspase‐3 caused by the transient expression of EGFP‐IPAS were increased by UVB irradiation. The C‐terminal region of IPAS mediated the UVB susceptibility of IPAS. Increase in IPAS‐induced mitochondrial clustering by UVB was completly inhibited by the p38 MAPK inhibitor SB203580. Mass spectrometry analysis of UVB‐activated IPAS identified several phosphorylation sites in the C‐terminal region containing p38 MAPK consensus phosphorylation sites at Ser219 and Ser223, and an MK2 consensus site at Ser184. Although mutations of Ser219 and Ser223 to Ala did not suppress the UVB‐induced mitochondrial clustering, replacement of Ser184 with Ala blocked it. A phosphomimetic substitution at Ser184 enhanced mitochondrial clustering and activation of caspase‐3 without UVB exposure. Furthermore, binding affinity to Bcl‐xL was increased by the mutation. Treatment of PC12 cells with CoCl2 caused activation of MK2 and mitochondrial clustering. IPAS‐dependent cell death induced by CoCl2 in PC12 cells was decreased by the treatment with the MK2 inhibitor MK2 inhibitor III and by siRNA‐directed silencing of MK2. Abstract : Inhibitory PAS is a proapoptotic protein and possibly associated with neurodegeneration of Parkinson's disease. IPAS induced perinuclear mitochondrial clustering that was augmented by UVB‐ and CoCl2 ‐induced activation of the p38 MAPK‐MK2 pathway. Mass analysis and subsequent mutational analysis demonstrated that phosphorylation of IPAS at Ser184 by MK2 was crucial for the enhancement of both mitochondrial clustering and apoptosis.